Maternal Educational Status as One of the Risk Factors Affecting the Incidence of Infants with Low Birth Weight in Dr. M. Soewandhie General Hospital Surabaya - Jihanifa Hega Salsabiila; Hermanto Tri Joewono; Sulistiawati Sulistiawati (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2021)
Introduction: Infants with low birth weight (LBW) was one of the main indicators of the cause of high infant mortality rates (IMR). The causes of IMR and maternal mortality rate (MMR) were determined by factors in maternal condition before and during pregnancy. In 2015, LBW in Surabaya reached 2.58%, namely a number of 1,261 of 48,783 born babies weighed. This study was performed by analyzing the effect of educational status as a risk factor affecting LBW in Dr. M. Soewandhie General Hospital Surabaya. Methods: This study used case control method with a retrospective approach using patient medical records as secondary data. The sample population were mothers who gave birth to infants with birth weight of 1,500 – 4,000 g in Dr. M. Soewandhie General Hospital Surabaya. The number of samples consisted of 80 patients with case and control ratio of 1:1. The sampling technique used was purposive sampling. Data collection techniques used variable data collection sheets taken from secondary data, namely medical records. Data analysis was performed by Chi-Square and Odds Ratio (OR) statistical tests. Results: Based on Chi-Square test, there was a relationship between educational status (p = 0.034) with the incidence of LBW. The results of this study indicated that the educational status of mothers that graduated from elementary school – senior high school was at risk of 9,750 times in delivering LBW. Conclusion: Educational status was the risk factor that had a correlation with LBW.